IIUM-fabricated portable electronic nose for halal authentication in beverages - Ab Mutalib, Nurul Asyikeen; Jaswir, Irwandi; Akmeliawati, Rini (2013)

(untitled)
This study has been successfully conducted to develop a method for rapid detection of ethanol (EtOH) content in beverages using portable electronic nose (E-Nose) prototype. E-Nose is a device that mimics human olfactory system and is widely used in food analysis. From previous studies, it was found that a portable device for the detection of halal compound is needed in the market. The portable electronic nose developed by International Islamic University Malaysia (IIUM)is found to be very reliable for the detection of EtOH in various beverages such as alcoholic beverages, isotonic drinks, soft drinks and fruit juices of different brands in Malaysia. The device has high accuracy and reliability, where it could detectEtOH conte nt as low as 0.1% (v/v). From the screening process,it was found that products that have halal label from the food producer itself has a small amount of ethanol present in the beverages.